2021
DOI: 10.1186/s13223-021-00590-x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular comorbidities of atopic dermatitis: using National Health Insurance data in Korea

Abstract: Background It is well known that atopic dermatitis (AD) is associated with other allergic diseases. Recentely, links to diseases other than allergic disease have also been actively studied. Among them, the results of studies regarding AD comorbidities, especially cardiovascular disease (CVD), have varied from country to country. Objective To analyze whether the risk of CVD is different between AD patients and healthy controls using Korean National … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…They found that patients with severe AD had a significant association with ischemic stroke, although misclassification of AD severity was present. By contrast, the Korean study by Jung et al (2021) using the National Health Insurance Data did not find any association between AD severity with stroke and myocardial infarction. In a Danish nationwide cohort study, Andersen et al (2016) found that patients with mild AD had decreased risk of cardiovascular adverse events.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…They found that patients with severe AD had a significant association with ischemic stroke, although misclassification of AD severity was present. By contrast, the Korean study by Jung et al (2021) using the National Health Insurance Data did not find any association between AD severity with stroke and myocardial infarction. In a Danish nationwide cohort study, Andersen et al (2016) found that patients with mild AD had decreased risk of cardiovascular adverse events.…”
Section: Discussionmentioning
confidence: 63%
“…This study employed a population-based design and a large sample size, but it had a shortcoming of misdiagnosis and lacked controlling for traditional risk factors such as diabetes, alcohol use, and cigarette smoking. Another Asian study using the Korean National Health Insurance Data demonstrated that AD cases had elevated stroke and myocardial infarction risk than those without AD, but there were no adjustments for covariates such as cigarette smoking and hypertension ( Jung et al, 2021 ). In addition to these Asian studies, some epidemiology data from other populations also showed positive associations of AD with ischemic stroke and coronary heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence indicates that AD is not only a dermatological disease but also an inflammatory disease that extends beyond the skin. Patients with AD have a greater risk of cardiovascular disorders than healthy controls, including stroke, myocardial infarction, angina, and peripheral vascular disease [ 32 ].…”
Section: Overview Of Ad and Treatment Optionsmentioning
confidence: 99%
“…Atopic dermatitis (AD) in children increases the risk of food allergies, asthma, allergic rhinitis, and other immune-mediated inflammatory diseases, as well as mental health disorders, and impairs not only the patients’ but also their family members’ quality of life. 1 2 3 4 …”
Section: Introductionmentioning
confidence: 99%